Perspektif Pasien dan Manajemen tentang Mutu Pelayanan IGD - Fachriza, Dicky; Aulia, Destanul; Rochadi, Kintoko (Jurnal Kesehatan, 2019)
The basic principle of a hospital is fulfilling the needs and demand of patients who hope that their health problems can be settled in a hospital. They expect ready, quick, responsive, and comfortable services. Patient satisfaction can be influenced by the health care quality of health care providers who sympathize, respect, and respond to their needs. The research used a qualitative method. The data were gathered by conducting participant observation, and in-depth interviews. The research subjects were 4 informants, IGD (emergency room) personnel and  IGD patients in Prima Inti Medika hospital. The result of the research, in the pre-service, showed that nurses’ response was quick, complaints were responded well, the process of inpatient and outpatient was good, nurses’ cooperation was good, and the personnel was accredited; but, the facility was inadequate and incentives were lower than the government’s standard. From the patients’ perspectives, it was found that pre-service was in accordance with SOP, the process of doctors’and pharmacy’s service was good, but nurses’ service and IGD facility were unsatisfactory, nurses’ cooperation was good, but their competence and quality were inadequate.